2020
DOI: 10.1007/s42242-020-00110-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro calcification studies on bioprosthetic and decellularized heart valves under quasi-physiological flow conditions

Abstract: The lifespan of biological heart valve prostheses available in the market is limited due to structural alterations caused by calcium phosphate deposits formed from blood plasma in contact with the tissues. The objective of this work is to present a comparative methodology for the investigation of the formation of calcium phosphate deposits on bioprosthetic and tissue-engineered scaffolds in vitro and the influence of mechanical forces on tissue mineralization. Based on earlier investigations on biological mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…D'Alessandro et al reported a model to assess the calcification potential of biological valves and found that the aldehyde groups have an effect on the activity of phospholipids, which could provide nucleation sites for Ca 3 (PO 4 ) 2 . [61,62] The toxicity of the aldehyde group leads to apoptosis, and the dead cells release phospholipids in response to enzymatic lysis, resulting in calcification. Gendler et al reported that the GA-fixed pericardium stored in a mixed solution of propylhydroxy-benzoate or methyl-hydroxy-benzoate and further washed three times with normal saline reduces the residual toxicity when implanted in mice.…”
Section: Residual Aldehyde Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Alessandro et al reported a model to assess the calcification potential of biological valves and found that the aldehyde groups have an effect on the activity of phospholipids, which could provide nucleation sites for Ca 3 (PO 4 ) 2 . [61,62] The toxicity of the aldehyde group leads to apoptosis, and the dead cells release phospholipids in response to enzymatic lysis, resulting in calcification. Gendler et al reported that the GA-fixed pericardium stored in a mixed solution of propylhydroxy-benzoate or methyl-hydroxy-benzoate and further washed three times with normal saline reduces the residual toxicity when implanted in mice.…”
Section: Residual Aldehyde Groupsmentioning
confidence: 99%
“…D’Alessandro et al. reported a model to assess the calcification potential of biological valves and found that the aldehyde groups have an effect on the activity of phospholipids, which could provide nucleation sites for Ca 3 (PO 4 ) 2 [61,62] . The toxicity of the aldehyde group leads to apoptosis, and the dead cells release phospholipids in response to enzymatic lysis, resulting in calcification.…”
Section: Mechanism and Influence Factors Of Biological Valve Calcific...mentioning
confidence: 99%
“…However, the safety in clinical application of Matrigel for HF regeneration is still unclear due to the tumor cell-derived source. Decellularized ECM (dECM) has been widely used due to its similar structural, biochemical, and biophysical properties as native tissues, allowing adequate mechanical and chemical support for tissue engineering [ 128 , 129 ]. Human placenta dECM (HPECM) hydrogel cultured with DPCs restored the protein expression that observed in vivo and the co-transplantation in nude mice regenerated de novo HF [ 25 ].…”
Section: Biomaterial-assisted Hair Follicle Regenerationmentioning
confidence: 99%
“…These bonds contain several active oxygen atoms capable of forming strong complexes with calcium cations. Calcification can be provoked by the bond of polymerized GA molecules, which is similar to pyridine bases found in bone tissue collagen [ 84 - 86 ], a degree of mineralization being directly dependent on the density of cross-links in the collagen matrix. In addition, the level of glycosaminoglycans and proteoglycans cross-linked with collagen and preventing spontaneous precipitation of calcium salts in soft tissues decreases in the biomaterial during conservation [ 87 - 89 ].…”
Section: The Use Of Bisphosphonates For the Modification Of Cardiovas...mentioning
confidence: 99%